Water Treatment Plants (WTPs) With High Efficiency Motors (HEMs) And Variable Speed Drives (VSDs) - Kadhim, Ghassan Jawad (2016)
The industrial sector especially (water treatment plant) is the largest consumer of energy in Malaysia with about 70% of the total electricity is consumed by electric motor driven pumps. The industrial sector contributes significantly to the national growth, and this economic growth drives the high growth in energy demand. Therefore, the increase in energy cost recently has created a situation where it has become essential to develop alternative energy technologies as well as improve efficiency. In this case, energy efficiency means reducing environmental degradation and increasing sustainability as well as cost savings. This dissertation proposes a completely new design of drives system in water treatment plant. This dissertation focuses on the economic benefits that can be obtained by replacing mechanical flow control of pumps with variable speed drive and replacing standard motors with new high efficiency motors at water treatment plants in Malaysia. Analyses had been carried out on a water treatment plant in Malaysia. This study explains the economic benefits of variable speed drive and high efficiency motors in water treatment plant industries. Based on the load profile before and after the installations, it has been estimated that there can be a total energy savings of 1862,263MWh, 2793,395MWh and 3724,529MWh by utilizing energy efficient motors for a 50%, 75% and 100% load respectively. and Similarly, it is hypothesized that a significant amount of energy can be saved using VSDs to reduce speed it is found that for 60 % to 10 % speed reduction can be reach to maximum and minimum value of energy savings of 7604,460MWh ,2015,640MWh, respectively. And it has been estimated that amounts of electric bill saving cost RM 234,702 (i.e. RM 2,816. 424) per year, the payback periods is 10 months. Energy savings up to 66.3% can be obtained for overall industry.